1998
DOI: 10.1038/29305
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of late-phase LTP is accompanied by PKA-dependent increase in AMPA receptor synthesis

Abstract: Long-term potentiation (LTP) is a form of synaptic plasticity that has been extensively studied as a putative mechanism underlying learning and memory. A late phase of LTP occurring 3-5 hours after stimulation and depending on transcription, protein synthesis and cyclic-AMP-dependent protein kinase (protein kinase A, or PKA) has been described, but it is not known whether transcription of presynaptic and/or postsynaptic genes is required to support late-phase LTP. Here we show that late-phase LTP can be obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(132 citation statements)
references
References 19 publications
4
125
1
Order By: Relevance
“…Activity-dependent recruitment of AMPARs is well described (Liao et al, 2001;O'Brien et al, 1998;Turrigiano, 2000) and is a final common pathway mediating activity-dependent changes in synaptic efficacy at CA1 excitatory synapses both in vivo and in vitro (Baudry and Lynch, 2001;Liao et al, 1995;Lledo et al, 1998;Nayak et al, 1998;Zamanillo et al, 1999). Activitydependent changes in synaptic function are primarily the consequence of intracellular Ca 2 þ -dependent biochemical cascades and involve changes in synaptic AMPAR number and/or function (Hayashi et al, 2000;Song and Huganir, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Activity-dependent recruitment of AMPARs is well described (Liao et al, 2001;O'Brien et al, 1998;Turrigiano, 2000) and is a final common pathway mediating activity-dependent changes in synaptic efficacy at CA1 excitatory synapses both in vivo and in vitro (Baudry and Lynch, 2001;Liao et al, 1995;Lledo et al, 1998;Nayak et al, 1998;Zamanillo et al, 1999). Activitydependent changes in synaptic function are primarily the consequence of intracellular Ca 2 þ -dependent biochemical cascades and involve changes in synaptic AMPAR number and/or function (Hayashi et al, 2000;Song and Huganir, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Long-lasting LTP, induced by a stimulation regimen similar to ours, was blocked when apical dendrites were severed from the cell bodies of CA1 pyramidal neurons in slices (Frey et al, 1989). Because LTP induced by this multitrain stimulation regimen is PKA dependent (Frey et al, 1993;Matthies and Reymann, 1993) and also requires the PKA-dependent synthesis of postsynaptic AMPA receptors for its expression (Nayak et al, 1998), these considerations support our hypothesis that postsynaptic mechanisms, including the activation of postsynaptic PKA, are critical for the expression of long-lasting, tetanus-induced LTP.…”
Section: Discussionmentioning
confidence: 99%
“…Translation inhibitors blocked this stimulation-induced synthesis (Osten et al 1996). In addition, it was reported that LTP induction stimulated the synthesis of glutamate receptor subunits GluR1 and GluR2/3, in a cAMP-signalling-mediated, transcriptiondependent manner (Nayak et al 1998). It would be interesting to see if synthesis of these plasticity-related proteins after LTP induction involves local translation mechanisms.…”
Section: Local Protein Synthesis During Synaptic Plasticity and Synapmentioning
confidence: 99%